2023
DOI: 10.3389/ffgc.2023.1082207
|View full text |Cite
|
Sign up to set email alerts
|

Lithological substrates influence tropical dry forest structure, diversity, and composition, but not its dynamics

Abstract: IntroductionTropical dry forests (TDF) are not only the most widespread tropical forest type but also the most threatened forest ecosystem worldwide. Yet, because their dynamics have been insufficiently studied, our knowledge about the factors responsible for the spatial and temporal variability in TDF dynamics remains very limited. In this study, we aimed (1) to assess the effects of two lithological substrates on TDF structure, diversity, and species composition, and (2) to determine whether and how these su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…on the Pacific watershed of the Isthmus of Tehuantepec. Mean annual temperature is 27.7°C, with a mean annual precipitation of 900 mm (Muñoz et al., 2023). Rainfall is highly seasonal, with 90% of the rainfall occurring between late May and mid‐October.…”
Section: Methodsmentioning
confidence: 99%
“…on the Pacific watershed of the Isthmus of Tehuantepec. Mean annual temperature is 27.7°C, with a mean annual precipitation of 900 mm (Muñoz et al., 2023). Rainfall is highly seasonal, with 90% of the rainfall occurring between late May and mid‐October.…”
Section: Methodsmentioning
confidence: 99%
“…Geomorphological factors (e.g., slope aspect and inclination, elevation, parental material) drive variation in soil properties and thus may influence plant community assembly (Baldeck et al., 2013 ; Durán et al., 2006 ; Guo et al., 2017 ; Rodrigues et al., 2019 ). Numerous studies in tropical forests have shown evidence that tree communities respond to the environmental heterogeneity associated with geomorphology and soils (e.g., Clark & Clark, 2000 ; Denslow et al., 2019 ; Durán et al., 2006 ; Fayolle et al., 2012 ; Guo et al., 2017 ; Jucker et al., 2018 ; Muñoz et al., 2023 ; Navarrete‐Segueda et al., 2021 ). However, studies focusing on liana communities are scarce (Addo‐Fordjour et al., 2014 ; DeWalt et al., 2006 ; Ibarra‐Manríquez & Martínez‐Ramos, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, more benign conditions, i.e., where limiting conditions do not strongly impact individual performance (such as milder temperatures, deeper and richer soils, and higher water availability) have been associated with more functionally diverse plant communities (Ding et al, 2019; Ottaviani et al, 2016; Spasojevic et al, 2013). The lithology and morphogenetic characteristics of geological substrates have effects on topography, soil nutrient availability, and soil physicochemical properties, all of which induce changes in species composition and abundance (de Souza et al, 2023; Durán et al, 2006; Gerrard, 1992; Muñoz et al, 2023; Pérez‐García et al, 2010). Geological substrate, a relevant factor for plant growth, can act as an environmental filter capable of shaping species distributions and functional diversity, depending on variations in the water retention potential and fertility of its derived soil (Fayolle et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the region of Nizanda (S Mexico), two different tropical dry forest communities occur, each one being associated with a different geological substrate (limestone or siliciclastic phyllite; Figure 1). Previous work in this region has shown that despite shared characteristics that warrant their classification as the same vegetation type (Pérez‐García et al, 2010), notable differences exist between them: the forest associated with limestone is more developed (e.g., it has higher basal area and density, and higher diversity), suggesting that it grows in a more benign habitat than its counterpart growing on phyllite (Muñoz et al, 2023). These contrasts motivated us to compare the functional diversity of these two tropical dry forest communities to test the hypothesis that geological substrate constitutes an environmental filter that shapes community leaf functional diversity.…”
Section: Introductionmentioning
confidence: 99%